Rationally Designed Dual‐Mesoporous Transition Metal Oxides/Noble Metal Nanocomposites for Fabrication of Gas Sensors in Real‐Time Detection of 3‐Hydroxy‐2‐Butanone Biomarker. (10th October 2021) - Ma, Junhao; Li, Yanyan; Li, Jichun; Yang, Xuanyu; Ren, Yuan; Alghamdi, Abdulaziz A.; Song, Guoxin; Yuan, Kaiping; Deng, Yonghui
Abstract: Transition metal oxides/noble metal (TMOs/NM) nanocomposites are one kind of important material for semiconductor gas sensors. The controllable construction of a highly connected mesoporous structure and easily accessible active sites is essential for gas sensing performance but remains a great challenge. Herein, a soluble mercapto phenolic resin polymer mediated co‐assembly approach is proposed for the construction of ordered dual mesoporous structure and the simultaneous loading of highly dispersed noble metal nanoparticles. The home‐made soluble mercapto phenolic resin polymer enabled the co‐assembly of transition metal precursors, noble metal precursors, and poly(ethylene oxide)‐block‐polystyrene (PEO‐ b ‐PS) micelles, resulting in a straightforward synthesis of ordered dual‐mesoporous TMOs/NM nanocomposites (e.g., WO3 /Au, TiO2 /Au, NbO x /AuPd). As proof of the concept, the synthesized dual‐mesoporous WO3 /Au materials are applied for sensing of 3‐hydroxy‐2‐butanone, a biomarker of food‐borne pathogenic bacteria Listeria monocytogenes . The sensors exhibit high sensitivity ( R a / R g = 18.8 to 2.5 ppm) and high selectivity based on their noble metal sensitization and superior mesopore connectivity for gas diffusion. Furthermore, the synthesized gas sensors are integrated into a wireless sensing module connected to a smartphone, providing a rapid and convenient real‐time detection of 3‐hydroxy‐2‐butanone. Abstract : A general one‐pot synthesis of ordered dual‐mesoporous transition metal oxides/noble metal nanocomposites is developed using a mercapto phenolic resin polymer as a multifunctional bridging molecule, which can realize multi‐component co‐assembly, stabilize the noble metal nanoparticles, and be a template for a secondary channel. The ordered dual‐mesoporous WO3 /Au realizes a rapid and convenient detection of 3‐hydroxy‐2‐butanone, a biomarker of Listeria monocytogenes .